Corporate zakat payment: A systematic literature review and bibliometric architecture (2010–2026) - Mohd Zaki, Adeeba Najihah; Ab Rahman, Siti Maziah (Journal of Islamic, Social, Economics and Development, 2026)
Corporate zakat payment represents a vital nexus between modern corporate governance and classical Islamic social finance, acting as an institutionalized mechanism for capital redistribution, poverty alleviation, and socio-economic justice. As business landscapes evolve, the literature tracking corporate zakat compliance, disclosure, and technological integration has proliferated extensively. This study presents a comprehensive systematic literature review (SLR) and bibliometric architecture of corporate zakat payment research indexed in the Scopus database from 2010 to 2026. Employing rigorous evaluative metrics and relational science mapping through a refined dataset of 415 scientific publications, this paper analyzes annual output trajectories, influential publishing outlets, prominent geographic contributors, and co-occurrence keyword networks. The analytical findings reveal an aggressive expansion in publication momentum post-2018, with Malaysia and Indonesia cementing undisputed intellectual leadership in the ASEAN region. The synthesized keyword networks expose a strategic evolutionary paradigm shift: progressing from foundational jurisprudence into structured corporate compliance behaviors, institutional governance frameworks, and cutting-edge digital transformations (including fintech, artificial intelligence, and blockchain-enabled smart contracts) aligned with the United Nations Sustainable Development Goals (SDGs). This paper provides critical theoretical and practical guideposts for Islamic finance scholars, institutional managers, and regulatory policy architects to map current research frontiers and navigate future empirical directions.